ADVANTAGES, DISADVANTAGES AND LIMITS OF APPLICATION PARTICIPATORY MODELS OF DEMOCRACY - Чабан, О.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The article contains an attempt to research the conceptual features of the theory of participatory democracy, for which extensive and constructive citizen participation is mandatory procedural component of the transformation of the political-administrative relations. Identifies strengths and weaknesses of participatory democracy. Defined the limits and risks of the use of participatory governance mechanisms.